2014
DOI: 10.2174/1871528112666131211102500
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Prevents Autoimmune-Associated Down- Regulation of p21 in Salivary Gland Cells Through a p53-Independent Pathway

Abstract: The submandibular salivary glands of non-obese diabetic (NOD) mice, a model for Sjogren’s syndrome and type-1 diabetes, show an elevated level of proliferating cell nuclear antigen (PCNA), a protein involved in cell proliferation and repair of DNA damage. We reported previously that epigallocatechin-3-gallate (EGCG), the most abundant green tea catechin, normalizes the PCNA level. PCNA’s activity can be regulated by the cyclin-dependent kinase inhibitor p21, which is also important for epithelial cell differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In autoimmune animal studies, we found that EGCG significantly reduced lymphocyte infiltration and serum autoantibody levels, and protects human cells from TNF-αinduced cytotoxicity [17,18]. Interestingly, our animal studies showed that EGCG modulates the antioxidant defense enzymes to protect cells from free radical-induced damage [19] and stabilizes p21 expression and reduces DNA damage from inflammation-induced reactive oxygen species [20]. Also, it has been widely reported that EGCG provides neuroprotective effects in preclinical studies and clinical trials [21][22][23].…”
Section: Introductionmentioning
confidence: 67%
“…In autoimmune animal studies, we found that EGCG significantly reduced lymphocyte infiltration and serum autoantibody levels, and protects human cells from TNF-αinduced cytotoxicity [17,18]. Interestingly, our animal studies showed that EGCG modulates the antioxidant defense enzymes to protect cells from free radical-induced damage [19] and stabilizes p21 expression and reduces DNA damage from inflammation-induced reactive oxygen species [20]. Also, it has been widely reported that EGCG provides neuroprotective effects in preclinical studies and clinical trials [21][22][23].…”
Section: Introductionmentioning
confidence: 67%
“…On the other hand, the regulatory role and pathological significance of the LINE-1 methylation pattern is indicated by the fact, that in patients with hypomethylated LINE-1 and with cyclin-dependent kinase-6 (CDK6) amplified esophageal squamous cell carcinoma the expression of P21 decreased [56]. This can be related to the antitumor effect of EGCG as well, as EGCG increases the expression of P21 tumor suppressor gene in vivo through hypomethylation of the promoter region of P21, irrespective of the P53 tumor suppressor-induced signaling pathway [30,57]-and P21 inhibits DNMT1 [30].…”
Section: Plos Onementioning
confidence: 99%
“…In autoimmune animal studies, we found that EGCG significantly reduces lymphocyte infiltration and serum autoantibody levels and protects human cells from TNF-α-induced cytotoxicity [ 20 , 21 ]. Interestingly, our animal studies showed that EGCG modulates the antioxidant defense enzymes to protect cells from free-radical-induced damage [ 22 ], stabilizes p21 expression, and reduces DNA damage from inflammation-induced reactive oxygen species [ 23 ]. Also, it has been widely reported in preclinical studies and clinical trials that EGCG provides neuroprotective effects [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%